If x , y , and z are real numbers that satisfy the following system of equations:
x 2 + 6 y y 2 + 1 2 z z 2 − 4 x = − 1 4 = − 6 3 = 2 8 ,
what is the value of ∣ x + y + z ∣ ?
This problem is posed by Danny H .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Out of several very similar correct solutions, this one is has is the most detailed one. Nicely done!
EDIT: It should be checked that ( x , y , z ) = ( 2 , − 3 , − 6 ) does indeed satisfy the system of equations. Of course, this is easily done.
I'd got the same idea from the general equation of a Cartesian equation of sphere
how do you write like this, like in my answer you can see my x^2 and yours how is your in style
Log in to reply
Check out the formatting guide button that is underneath the text area when you write a solution. It's L A T E X !
Type \ Then ( then x^2 then \ then ).
Add all three equations, rearrange, and factor to obtain ( x − 2 ) 2 + ( y + 3 ) 2 + ( z + 6 ) 2 = 0 By the trivial inequality, ( x , y , z ) = ( 2 , − 3 , − 6 ) so ∣ x + y + z ∣ = 0 0 7 .
Nicely done!
If you're going to write "7" as "007", a Bond reference is obligatory. ;)
Beautiful!
how do you write like this, like in my answer you can see my x^2 and yours how is your in style
Log in to reply
You'd have to place your code with brackets: \ ( code \ )
You can refer to the Math formatting guide for more details.
Add up the given eqns
x^2+6y+y^2+12z+z^2-4x=-49
(x^2-4x)+(y^2+6y)+(z^2+12z)+49=0
(X^2-4x+4)+(y^2+6y+9)+(z^2+12z+36)=0
(X-2)^2+(y+3)^2+(z+6)^2=0
Sum of three squared terms zero implies all terms are zero
X=2, y=-3, z=-6
X+y+z=-7
You still have to check that the particular value of ( x , y , z ) satisfies the three equations individually.
Note that ( x 2 + 6 y ) + ( y 2 + 1 2 z ) + ( z 2 − 4 x ) = ( − 1 4 ) + ( − 6 3 ) + ( 2 8 ) , so ( x 2 − 4 x ) + ( y 2 + 6 y ) + ( z 2 + 1 2 z ) = − 4 9 . Thus ( x 2 − 4 x + 4 ) + ( y 2 + 6 y + 9 ) + ( z 2 + 1 2 z + 3 6 ) = − 4 9 + 4 + 9 + 3 6 = 0 , which could be restated as ( x − 2 ) 2 + ( y + 3 ) 2 + ( z + 6 ) 2 = 0 . Since a square is never negative, it is 0 if and only if its square root is 0 , and the sum of ( x − 2 ) 2 , ( y + 3 ) 2 and ( z + 6 ) 2 is 0 , all of x − 2 , y + 3 , and z + 6 is 0 . Therefore x = 2 , y = − 3 , and z = − 6 . Note that x + y + z = − 7 , so ∣ x + y + z ∣ = 7 .
I think that you have to scroll to the right to see the whole solution
how do you write like this, like in my answer you can see my x^2 and yours how is your in style
Adding the three equations we get
x^2 +y^2+z^2 -4x+6y+12z+49=0 or,
(x-2)^2+(y+3)^2+(z+6)^2=0
sum of squares of real numbers adding to zero ??
since square of a real number is always positive and they are adding to zero hence the solution.
x=2 , y=-3 , z=-6 . therefore |x+y+z|=7.
I did this by trying different values for x and y, starting with 1. Using 1 for x, we get (6y = -15), which doesn't work as x, y and z are all integers. Then trying 2 for x we get (6y = -18, so y = -3.) Substituting this into the second equation, we get 1(2z = -72), so (z = -6). Checking these in the third equation, we get (36 - 8 = 28), which is correct. Therefore (x +y + z = -7), so the answer is 7.
Add the equations and we get x 2 − 4 x + y 2 + 6 y + z 2 + 1 2 = − 4 9
Through completing the square, we get ( x − 2 ) 2 − 4 + ( y + 3 ) 2 − 9 + ( z + 6 ) 2 − 3 6 = − 4 9
( x − 2 ) 2 + ( y + 3 ) 2 + ( z + 6 ) 2 = 0
The only way for this to be true is for every bracket to be equal to 0 , and so x = 2 , y = − 3 , z = − 6
Therefore ∣ x + y + z ∣ = ∣ − 7 ∣ = 7
how do you write like this, like in my answer you can see my x^2 and yours how is your in style
We add the 3 equations and factor to get
( x − 2 ) 2 + ( y + 3 ) 2 + ( z + 6 ) 2 = 0
Since a 2 ≥ 0 for all real values of a we must have
( x − 2 ) 2 = 0
( y + 3 ) 2 = 0
( z + 6 ) 2 = 0
x = 2 , y = − 3 , z = − 6
∣ x + y + z ∣ = 7
how do you write like this, like in my answer you can see my x^2 and yours how is your in style
The equation is equivalent to $$(z+6)^2+(x-2)^2+(y+3)^2=0$$ Thus, $z=-6,x=2,y=-3$. We get $|x+y+z|=7$.
first eqn =(1), second eqn =(2), third =(3)
( 1 ) + ( 2 ) + ( 3 ) = x 2 − 4 x + y 2 + 6 x + z 2 + 1 2 z = − 4 9
= > ( x − 2 ) 2 + ( y + 3 ) 2 + ( z + 6 ) 2 = 0 ∴ x = 2 , y = − 3 , z = − 6 .
X²+y²+z²-4x+6y+12z+49=0 (x-2)²+(y+3)²+(z+6)²=0 x=2 y=-3 z=-6 |x+y+z|=|2-3-6|=7
By adding the three equations and completing the squares, we obtain the equation ( x − 2 ) 2 − 4 + ( y + 3 ) 2 − 9 + ( z + 6 ) 2 − 3 6 = − 4 9 , or in other words, ( x − 2 ) 2 + ( y + 3 ) 2 + ( z + 6 ) 2 = 0 , which has exactly one real solution: ( x , y , z ) = ( 2 , − 3 , − 6 ) . The requested value then is ∣ x + y + z ∣ = ∣ − 7 ∣ = 7 .
adding the three equations and completing the square we get (x-2)^2+(y+3)^2+(z+6)=0.
Sum of squares of real numbers is zero only when they are all zero. Therefore x=2 ,y=-3,z=-6.
Hence |x+y+z|=7
Add the equations and complete the square for each variable. The result is ( x − 2 ) 2 + ( y + 3 ) 2 + ( z + 6 ) 2 = 0 . Clearly, each term must equal zero! So x = 2 , y = − 3 , z = − 6 , and ∣ x + y + z ∣ = 7 .
Problem Loading...
Note Loading...
Set Loading...
Adding the three equations together yields: x 2 − 4 x + y 2 + 6 y + z 2 + 1 2 z = − 4 9
We can now complete the squares on the left side: x 2 − 4 x + 4 + y 2 + 6 y + 9 + z 2 + 1 2 z + 3 6 = − 4 9 + 4 + 9 + 3 6 ( x − 2 ) 2 + ( y + 3 ) 2 + ( z + 6 ) 2 = 0
For the sum of squares of real numbers to be 0 , each number must be 0 .
Hence, x − 2 = y + 3 = z + 6 = 0 ⇝ ( x , y , z ) = ( 2 , − 3 , − 6 ) .
Therefore, ∣ x + y + z ∣ = ∣ 2 − 3 − 6 ∣ = 7 .